The determinants of destination attractiveness of Danang for domestic tourists in the context of the impact of Covid-19 - Lê Thái Phượng; Tô Văn Hạnh; Phạm Thị Chi (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2022)
The study aims to determine the attractive components and attributes of Danang destinations for domestic tourists in the context of Covid-19. Qualitative methods through expert interviews combined with the quantitative method used in this study. The results show that the destination attractiveness of Danang for domestic tourists in the context of the impact of Covid-19 is composed of 08 dimensions (33 attributes), including (1) Natural; (2) Cultural; (3) Activities, festivals, events; (4) Tourism facilities; (5) Infrastructure, security, and safety; (6) Prices of products and services; (7) Visitors’ perception of the Covid-19; (8) Stimulus policy. The research results contribute to proposing orientations for Danang tourism management agencies and tourism businesses to come up with solutions to improve the destination attractiveness of Danang and attract domestic tourists coming to Danang after the Covid-19 pandemic was under control.